Gen Z Wajib Tau! Edukasi dan Penguatan Pasal-Pasal UUD 1945 bagi Generasi Z (Pasca Milenal) bagi Siswa-Siswi SMA Negeri 4 Takengon - Seri Mughni Sulubara; Yury Ulandary; Riska Riska; Desi Purnama Sari (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
This community service was carried out for students of SMA Negeri 4 Takengon Paya Tumpi, Takengon-Bireuen Road, Pinangan Village. The problem faced has not been done education and strengthening understanding of the articles contained in the 1945 Constitution. The purpose of the study was to examine the extent of understanding of SMA Negeri 4 Takengon students as Generation Z to be able to have the ability to understand the articles contained in the 1945 Constitution. The method used is qualitative research through surveys, preparation, coordination and implementation of community service activities. The result of the research is that students can understand the meaning of the articles of the 1945 Constitution. By understanding the articles of the 1945 Constitution, it can foster a sense of nationalism, love for the country and the spirit of patriotism among Generation Z, especially students of SMA Negeri 4 Takengon.